Improving child nutrition outcomes in India : can the integrated child development services be more effective? - Das Gupta, Monica, 1975- 1975- (Policy research working paper, 2005)
"Levels of child malnutrition in India fell only slowly during the 1990s, despite significant economic growth and large public spending on the Integrated Child Development Services (ICDS) program, of which the major component is supplementary feeding for malnourished children. To unravel this puzzle, the authors assess the program's placement and its outcomes using National Family Health Survey data from 1992 and 1998. They find that program placement is clearly regressive across states. The states with the greatest need for the program - the poor northern states with high levels of child malnutrition and nearly half of India's population - have the lowest program coverage and the lowest budgetary allocations from the central government. Program placement within a state is more progressive: poorer and larger villages have a higher probability of having an ICDS center, as do those with other development programs or community associations. The authors also find little evidence of program impact on child nutrition status in villages with ICDS centers. "--World Bank web site